Rozwój rolnictwa ekologicznego w Polsce - Kowalska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Since 1999 organic agriculture in Poland has been developing intensively. In 2005 there were 7183 organic farms which occupied the area of 167 740 hectares. The biggest number of organic farms were located in małopolskie, podkarpackie, świętokrzyskie, and lubelskie provinces. Growth in the number of large farms (over 10 hectares) was noticed. Dynamic growth in the area of meadows, postures, orchard. and blueberry plantations has been noticed in the last few years. Since 2003 a dynamic development in organic food processing industry, especially in the area of fruit, vegetable and crops processing, has been observed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 195-202